The effect of carbon nanotube chirality on the spiral flow of copper atoms in their cores - Lim, M. C. G. (2013)
The effect of carbon nanotube (CNT) chirality on the flow of copper atoms along its core has been investigated using molecular dynamics simulations. The investigation is conducted using CNTs of different chirality, and different flow conditions such as temperatures, bias voltages and the initial positions of the copper atoms. The results show that the atoms flow in a spiral fashion along the CNT channels. The effect is most evident in the CNT channel with zigzag CNTs. The movement of the copper atoms is more erratic when the temperature is increased at a low biased voltage, regardless of the types of channel used. The initial positions of the copper atoms affect the way they converge as they move downstream along the channel. A bias voltage of 4 V favours the initiation of a spiral flow, especially when the position of the copper atoms is far from the central axis of the channel.